2018
DOI: 10.1371/journal.pone.0201475
|View full text |Cite
|
Sign up to set email alerts
|

Vertically and horizontally directed muscle power exercises: Relationships with top-level sprint performance

Abstract: The capacity to rapidly generate and apply a great amount of force seems to play a key role in sprint running. However, it has recently been shown that, for sprinters, the technical ability to effectively orient the force onto the ground is more important than its total amount. The force-vector theory has been proposed to guide coaches in selecting the most adequate exercises to comprehensively develop the neuromechanical qualities related to the distinct phases of sprinting. This study aimed to compare the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 28 publications
(40 reference statements)
7
78
1
4
Order By: Relevance
“…For those with unilateral spasticity (ie, FT7), positive relationships were found between high accelerations and SBJ performance. This result matches with a recent finding by Loturco et al, 36 who demonstrated that hip-thrust jumps (ie, horizontal jumps such as SBJ) are more associated with the maximum acceleration phase in sports performance. In FT8 players, the positive relationship between SJ and Vel max is similar to that obtained by Beckman and Tweedy, 37 who demonstrated that SJ had a low correlation with sprint performance (30 m sprint).…”
supporting
confidence: 92%
“…For those with unilateral spasticity (ie, FT7), positive relationships were found between high accelerations and SBJ performance. This result matches with a recent finding by Loturco et al, 36 who demonstrated that hip-thrust jumps (ie, horizontal jumps such as SBJ) are more associated with the maximum acceleration phase in sports performance. In FT8 players, the positive relationship between SJ and Vel max is similar to that obtained by Beckman and Tweedy, 37 who demonstrated that SJ had a low correlation with sprint performance (30 m sprint).…”
supporting
confidence: 92%
“…In the present study, important correlations were found between the loads needed to reach 10%, 30%, and 50% of Vloss, sprint, and jump variables. Our results indicate that Vmax showed moderate to strong correlations with JH in both jumps, which is in line with those found in elite sprinters [26], track and field athletes [32], professional rugby league players [33], and rugby union players [34]. These findings are supported not only by the fact that jump height was correlated to Vmax, but also because unresisted and RST times (i.e., T 30-20BM, T 30-40BM, T 30-60BM, T 30-80BM) were strongly correlated to both jumping tasks and Vmax.…”
Section: Discussionsupporting
confidence: 91%
“…The most noticeable difference between sprinting and jumping is that the former requires the resultant force and power to be more horizontally directed, while the latter requires a vertical orientation of the abovementioned variables [35]. Nevertheless, in the later phases of sprint, where the athletes are running close to or at Vmax, vertically oriented tasks (i.e., jumping) seem to be closely associated [32]. These findings have useful implications for practitioners in the way that JH and Vmax could be used not only to identify talent and monitor training, but also as resistance training strategies, where the aim should be placed on maximizing jumping ability and, hence, sprint performance.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed markers such as acceleration (r=0.93 ;Loturco, et al 2018). Furthermore, Contreras, et al (2017) recently compared 6-weeks of strength training using either a front squat or BHT exercise on performance markers in adolescent males.…”
Section: Introductionmentioning
confidence: 99%